The Labor Market Returns to Very Short Postsecondary Certificates - Rajeev Darolia; Chuanyi Guo; Youngran Kim (Institute of Labor Economics (IZA), 2023)
Major policy initiatives and high award rates have led to questions about the value of short-term postsecondary credentials. We examine the labor market returns to very short certificates, including those that require only a few credits to complete, using data from a state that has among the highest awarding rates of such credentials. We do not find strong evidence that rapid certificates (those that require 6 credits or fewer) have lower immediate labor market returns than longer but still short-term certificates (7-36 credits). For health students, rapid certificates yield the greatest immediate earnings and employment gains, though these benefits appear to fade out. We also find that, compared to pre-enrollment, health and skilled trades students who earned a rapid certificate are most likely to switch into an establishment whose industry aligns with the field of study.
Keywords: I26; J24; J38; 330; returns to education; postsecondary certificates